Performance of Polydioxanone-Based Membrane in Association with 3D-Printed Bioceramic Scaffolds in Bone Regeneration - Pitol-Palin, Letícia [UNESP]; Frigério, Paula Buzo [UNESP]; Moura, Juliana [UNESP]; Pilatti, Livia; de Oliveira, Letícia Marques Jordão; Matsubara, Elaine Yoshiko; Tunchel, Samy; Shibli, Jamil Awad; Blay, Alberto; Saska, Sybele; Okamoto, Roberta [UNESP] (MDPI, 2023)
This study evaluated the bioactivity of 3D-printed β-tricalcium phosphate (β-TCP) scaffolds or hydroxyapatite (HA) scaffolds associated with polydioxanone (PDO) membrane (Plenum® Guide) for guided bone regeneration in rats. Fifty-four rats were divided into three groups (n = 18 animals): autogenous bone + PDO membrane (Auto/PG); 3D-printed β-TCP + PDO membrane (TCP/PG); and 3D-printed HA + PDO membrane (HA/PG). A surgical defect in the parietal bone was made and filled with the respective scaffolds and PDO membrane. The animals were euthanized 7, 30, and 60 days after the surgical procedure for micro-CT, histomorphometric, and immunolabeling analyses. Micro-CT showed an increase in trabecular thickness and a decrease in trabecular separation, even with similar bone volume percentages between TCP/PG and HA/PG vs. Auto/PG. Histometric analysis showed increased bone formation at 30 days in the groups compared to 7 days postoperatively. Immunolabeling analysis showed an increase in proteins related to bone formation at 30 days, and both groups showed a similar immunolabeling pattern. This study concludes that 3D-printed scaffolds associated with PDO membrane (Plenum® Guide) present similar results to autogenous bone for bone regeneration.
Keywords: 3D-printed scaffolds; additive manufacture; bone regeneration; guided tissue regeneration; hydroxyapatite; polydioxanone; synthetic polymer; β-tricalcium phosphate